Polymorphic Nucleotide within the Promoter of Nitrate Reductase (NarGHJI) Is Specific for Mycobacterium tuberculosis - Stermann, Marion (American Society for Microbiology, 2003)
Mycobacterium tuberculosis rapidly reduces nitrate, leading to the accumulation of nitrite. This characteristic served for the past 40 years to differentiate M. tuberculosis from other members of the Mycobacterium tuberculosis complex (MTBC), such as Mycobacterium bovis (non-BCG [referred to here as simply “M. bovis”]), Mycobacterium bovis BCG, Mycobacterium africanum, or Mycobacterium microti. Here, a narG deletion in M. tuberculosis showed that rapid nitrite accumulation of M. tuberculosis is mediated by narGHJI. Analysis of narG mutants of M. bovis and M. bovis BCG showed that, as in M. tuberculosis, nitrite accumulation was mediated by narGHJI, and no other nitrate reductase was involved. However, in contrast to M. tuberculosis, accumulation was delayed for several days. Comparison of the narGHJI promoter revealed that, at nucleotide −215 prior to the start codon of narG, M. tuberculosis carried a thymine residue, whereas the bovine mycobacteria carried a cytosine residue. Using LightCycler technology we examined 62 strains of M. tuberculosis, M. bovis, M. bovis BCG, M. microti, and M. africanum and demonstrated that this single nucleotide polymorphism was specific for M. tuberculosis. For further differentiation within the MTBC, we included, by using LightCycler technology, the previously described analysis of oxyR polymorphism, which is specific for the bovine mycobacteria, and the RD1 polymorphism, which is specific for M. bovis BCG. Based on these results, we suggest a LightCycler format for rapid and unambiguous diagnosis of M. tuberculosis, M. bovis, and M. bovis BCG.